Effect of Length of External Bar at Soffit on the Performance of Retrofitted RC Beams – A Finite Element Study - Vasudevan, G.; Kothandaraman, S. (Проблемы прочности, 2017)
This paper presents the results of the finite element study on the effect of length of the external bar at soffit on the flexural behavior of retrofitted RC beams. A reference beam specimen and five retrofitted beam specimens with external bar length as variable were analysed using ANSYS 12.0 software and the results are presented. Initial cracking, performance at yielding of internal bar and at ultimate stage, ductility behavior, formation and propagation of cracks were studied and reported in this paper. Представлены результаты конечноэлементного расчета прогиба модифицированных железобетонных перекрытий с учетом влияния длины внешнего потолочного бруса. С помощью программного пакета ANSYS 12.0 выполнен расчет напряженно-деформированного состояния пяти образцов модифицированных железобетонных перекрытий, усиленных внешним брусом различной длины, и тарировочного образца. Исследованы процессы зарождения трещин, поведение перекрытий при пластической деформации внутреннего бруса и на стадии разрушения, а также закономерности формирования и распространения трещин. Наведено результати скінченноeлементного розрахунку прогину модифікованого залізобетонного перекриття з урахуванням впливу довжини зовнішнього стельового бруса. За допомогою програмного пакета ANSYS 12.0 розраховано напруженодеформований стан п яти зразків модифікованого залізобетонного перекриття, підсиленого зовнішнім брусом різної довжини, і тарувального зразка. Досліджено процеси зародження тріщин, поведінку перекриттів за пластичної деформації внутрішнього бруса і на стадії руйнування, а також закономірності формування і розповсюдження тріщин.